The Phenomenon of Purchasing Instagram Blue Tick Among Students at Swadaya Gunung Jati University in Cirebon - Bayu Pratama Al-farizi; Siti Khumayah; Farida Nurfalah (Indonesian Journal Publisher, 2026)
The presence of the Meta Verified feature on Instagram shifts the paradigm of digital authenticity from organic reputation to an economy-based symbol. This study aims to analyze the motivations of students at Gunung Jati University (UGJ), the social meaning, and the social validation obtained through the purchase of blue ticks. The research method used is descriptive qualitative. Data was collected through in-depth interviews with four informants, participant observation of account activities, and a study of documentation sourced from scientific journals and textbooks to strengthen the validity of the findings. The results of the study show that the informants' motivation was driven by the processing of impressions to build visual credibility. From a communication perspective, the active use of the blue tick plays a role in creating self-identity in the digital public sphere. In addition, possession of the verification symbol triggers an increase in digital literacy, whereby users become more careful and selective when managing content. Technical and social validation has been proven to improve students' self-concept as it brings social status recognition. The research conclusion confirms that the blue tick for students is a commodity of prestige that provides symbolic satisfaction and legitimizes their position in both digital and real social stratification.